Extending abbreviated error‐correction assessments to adults with intellectual or developmental disabilities. (13th July 2022) - Braren, J. Turner B.; Samaha, Andrew L.; Livingston, Cynthia; Cividini‐Motta, Catia; DePaolo, Karie S.
Abstract: We extended Carroll et al. (2018) by evaluating the predictive validity of an abbreviated error‐correction assessment (abbreviated assessment) for four adults with intellectual or developmental disabilities. One abbreviated assessment and one validation assessment were conducted for each participant. We used a ranking procedure similar to Carroll et al. to analyze results of the abbreviated assessment and identify the most efficient error‐correction procedure (ECP) for each participant. Results showed high correspondence between the ECP identified during the abbreviated assessment and the most efficient ECP identified during the validation assessment for one of four participants, and moderate‐to‐low correspondence for the remaining three participants. Each participant's average rate of responding during each ECP was comparable across abbreviated and validation assessments, so we conducted statistical analyses to evaluate the strength of relation (Pearson's r ) between assessment results. Overall, there was high correspondence between measures taken during both assessments for all participants.